The Rise and Fall of Chanco Cheese in Chile (1860-1930) [el Auge y Caída del Queso Chanco en Chile (1860-1930)] - Lacoste, P; Soto-González, N (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2015)
This paper studiesthe historical evolution of Chanco cheese during two very different time periods: 1860-1900and 1900-1930. The former was characterized by a high presence of the aforementioned cheesein Chilean society, and the latter period encompassed a time of identity contamination. UnlikePisco, which has been delimited and protected as an Appellation of Origin (AO), Chancocheese has been a victim of dilution of its own identity and cultural value. We hypothesizethat the dilution and devaluing of Chanco cheese was a result of the incoherent actions of theState, producers and merchants with respect to its assessment, protection and delimitation ofits identity. © 2015, Ciencia e Investigacion Agraria. All right reserved.